Pengaruh Gaya Kepemimpinan Partisipatif Dan Kedisiplinan Lurah Terhadap Partisipasi Masyarakat Dalam Pembangunan Di Wilayah Kelurahan Cikiwul Kecamatan Bantargebang - Puji Iskandar; Wahidin Septa Zahran; Renisya Ayu Utami (Jurnal Ilmu Administrasi Publik, 2023)
The objective of this study is to find out how  much  the  influence  of  Participative Leadership Style and Village Disciplinary to the Community Participation in Cikiwul Village, partially and simultaneously. Sample in this study is amounting to 99 residents of  Cikiwul  Village. This study used quantitative descriptive research methodology. Result of the study identified that Participative  Leadership  Style  in  the  amount  of 95.5% affected to the Community And t_count test identified that there is positive and significant influence of the Village Head Disciplinary in the amount of 40.7% affected to the Community Participation and tcount test identified that there is positive and significant influence. Simultaneous test identified that community leadership        and        disciplinary        of         the Village         head         affected         50.5% to the Community Participation. Based on Anova F test, it is found that Sig value is in the amount of 0,000 < 0,05, so it can be concluded that Participative Leadership Style (X1) and Village Head Disciplinary (X2) simultaneously affected to the Community Participation (Y).